EKSPLORASI DAMPAK KUALITAS PRODUK TERHADAP NIAT BELI ULANG: PERSPEKTIF MEDIASI KEPUASAN PELANGGAN - Damayanti, Sepri Putri (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
For most women, taking care of their skin is essential to maintaining their beauty. In order to better understand how Scarlett users' purchase actions affect their overall level of satisfaction, this study will assess the direct and indirect effects of product quality and price on customer satisfaction. Utilizing a quantitative methodology, 114 respondents participated in this research. This study used a purposive sampling technique. The research use the causal design technique to examine the hypotheses that are produced. To ascertain the link between independent and dependent variables, structural equation modeling (SEM) via Smart-PLS version 4.0 (SEM) is the analytical tool utilized. The results of the study demonstrate that repurchase intention is positively and significantly impacted by product quality. The study's findings show that repurchase intention is positively and significantly impacted by product quality. On the other hand, using customer satisfaction as an mediator, product quality significantly positively affects the desire to repurchase.